Investigating the role of mitochondrial DNA D-loop variants, haplotypes, and copy number in polycystic ovary syndrome: implications for clinical phenotypes in the Chinese population - Chen, Yang; Wu, Wei-jia; Xing, Li-wei; Zhang, Xiao-juan; Wang, Jing; Xia, Xiao-yan; Zhao, Rui; Zhao, Rong (Frontiers in Endocrinology, 2023)
Background The presence of genetic variations in mitochondrial DNA (mtDNA) has been associated with a diverse array of diseases. The objective of this study was to examine the correlations between mtDNA D-loop, its haplotypes, and polycystic ovary syndrome (PCOS) in the Chinese population, as well as the associations between mtDNA D-loop and symptoms of PCOS. The study also sought to determine whether the mtDNA copy number in Chinese patients with PCOS differed from that of individuals in the control group. Methods Infertile individuals who only had tubal or male factor treatment were the focus of research by TCGA and GEO. mtDNA haplotypes were categorized using polymorphic D-loop sites. mtDNA D-loop, PCOS features, and mtDNA haplotypes were analyzed using R software to determine the strength of the association between the three. There are certain DNA haplotypes linked to PCOS. Microdroplet digital Polymerase chain reaction (PCR) was used to determine the mt DNA copy number in a convenience sample of 168 PCOS patients and 83 controls. Results Among the research group, the majority of D-loop mutations were infrequent (frequency < 1%), with only 45 variants displaying a minimum allele frequency (MAF) of 5% or higher. No association was found between polymorphism loci in PCOS patients and body mass index (BMI). Noteworthy, C194T, 1A200G, 523delAC, and C16234T showed positive correlations with elevated LH/FSH levels. Additionally, specific polymorphic loci G207A, 16036GGins, and 16049Gins within the D-loop region of mtDNA potentially exerted a protective role in PCOS development. Conversely, no statistical significance was observed in the expression levels of C16291T and T489C. Chinese women with mtDNA haplotype A15 exhibited a decreased risk of developing PCOS. Moreover, a significant difference in mtDNA copy number was detected, with controls averaging 25.87 (21.84, 34.81), while PCOS patients had a mean of 129.91 (99.38, 168.63). Conclusion Certain mtDNA D-loop mutations and haplotypes appear to confer protection against PCOS in Chinese women. Also, elevated mtDNA copy number may serve as an indicator during early stages of PCOS.